Randomized, single‐centre, double‐blinded repeated dose investigation of safety and tolerability of ocular administrations of a novel silica eye drop product in healthy volunteers - Poluianova, Aleksandra; Akieh‐Pirkanniemi, Marceline N.; Hartikainen, Arto; Arstila, Hanna; Kaarniranta, Kai; Leino, Lasse (Wiley, 2026)
Purpose
Managing ocular diseases often requires frequent eye drop administration, which can challenge patient compliance. A long-acting eye drop technology using an amorphous synthetic silica composite was developed to address this. Our study aimed to assess the safety and tolerability of the Silica Eye Drop platform in healthy volunteers over 15 days.
Methods
Twelve healthy volunteers participated in a randomized, double-blinded, placebo-controlled trial of the Silica Eye Drop Product, containing no active substance. Participants received one drop in one eye daily for 13 days, with the other eye serving as an untreated control. Safety and tolerability were evaluated through various examinations at multiple time points. Ocular discomfort was assessed with a questionnaire at these times, and additional evaluations of lens, vitreous body, visual acuity (BCVA), ocular protection index (OPI), and intraocular pressure (IOP) were performed at t0 and D15.
Results
No significant differences in ocular metrics between treated and untreated eyes were observed after 15 days of Silica Eye Drop application (IOP: control 14.1 ± 2.02 mmHg, treated 13.6 ± 1.75 mmHg; BCVA: control 1.22 ± 0.16, treated 1.24 ± 0.15; OPI: control 1.66 ± 0.43, treated 1.63 ± 0.40). Questionnaire responses indicated that 68% of volunteers experienced mild discomfort during the product application, while 32% noted moderate discomfort. The average pleasantness score was 4.9 ± 1.83 using a 10-point scale, indicating acceptable tolerability of Silica Eye Drops.
Conclusions
The findings suggest that Silica Eye Drops are safe and well-tolerated by study subjects when used once daily. This supports further developing sustained release topical ocular products for delivering pharmacological treatments in various eye conditions.